A Qualitative Study of Quality of Life Concerns following a Melanoma Diagnosis - Rachel I. Vogel; Lori G. Strayer; Rehana L. Ahmed; Anne Blaes; DeAnn Lazovich (Journal of Skin Cancer)
The goal of this study was to identify a relevant and inclusive list of quality of life issues among long-term survivors of melanoma. Individuals diagnosed with stage I-III cutaneous melanoma and had survived 1-5 years, ages 18-65 years at diagnosis, were recruited. Five focus groups were conducted with 33 participants in total. Discussions centered on participants’ experiences at diagnosis, as well as ongoing physical, emotional, and social concerns, and behavioral changes since diagnosis. The majority of participants reported shock, fear, and feeling overwhelmed at the time of diagnosis. Some reported lingering physical concerns, including pain, numbness, and lymphedema, while a few reported no lasting issues. Emotional concerns were common, with most reporting anxiety. Several also noted feeling lonely and isolated. Social concerns included alteration of activities to avoid sun exposure, issues with family communication, and frustration with the lack of appreciation of the seriousness of melanoma by others. Finally, while many participants reported changes to their sun exposure and UV-protection behaviors, some reported little to no change. The shared experiences among participants in this study confirm the unique nature of melanoma and the need for interventions designed to improve the health and quality of life of melanoma survivors.